2015
DOI: 10.1177/0194599815617126
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Difference in Postthyroidectomy Hypocalcemia

Abstract: In this study, patients undergoing thyroidectomy in the winter months were more likely to develop postoperative hypocalcemia when compared with those operated in the summer. Further studies are needed to understand the role of vitamin D in the observed seasonal difference in hypocalcemia rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Another single paper assessed the connection with season and found that patients who underwent thyroidectomy in winter developed biochemical hypocalcaemia more frequently than those who had their operation in the summer months. 62…”
Section: Resultsmentioning
confidence: 99%
“…Another single paper assessed the connection with season and found that patients who underwent thyroidectomy in winter developed biochemical hypocalcaemia more frequently than those who had their operation in the summer months. 62…”
Section: Resultsmentioning
confidence: 99%
“…Mascarella et al found significant differences in the rates of hypocalcaemia between the following months: winter (8.3%); spring (7.3%); summer (1.3%); autumn (3.5%). Thyroidectomy performed in winter was significantly associated with temporary hypocalcaemia in multivariable analysis (32).…”
Section: Vitamin Dmentioning
confidence: 94%
“…Our previous survey study showed that a majority (57%) of surgeon members of the ATA and the International Association of Thyroid Surgeons who responded to the survey do not recommend checking vitamin D levels prior to thyroidectomy 20 . One of the factors that increased the likelihood for surgeons to check vitamin D levels was practicing in the Northeast region of the United States, which could be attributed to the increased risk of developing hypocalcaemia in areas with significant winter seasons 21 . Interestingly, there was no significant difference between surgeons practicing in the United States vs other countries, as was seen with endocrinologists.…”
Section: Discussionmentioning
confidence: 99%
“…20 One of the factors that increased the likelihood for surgeons to check vitamin D levels was practicing in the Northeast region of the United States, which could be attributed to the increased risk of developing hypocalcaemia in areas with significant winter seasons. 21 Interestingly, there was no significant difference between surgeons practicing in the United…”
Section: Ta B L E 1 Check Preoperative Vitamin D Levels To Predict Postoperative Hypocalcaemiamentioning
confidence: 99%